Formation and Characterization of a BeOBeC Multiple Radical Featuring a Quartet Carbyne Moiety. (3rd March 2020) - Li, Wan‐Lu; Zhang, Qingnan; Chen, Mohua; Hu, Han‐Shi; Li, Jun; Zhou, Mingfei
Abstract: Through reaction of beryllium dimers with carbon monoxide, a carbonyl complex BeBeCO is formed in solid neon. Upon visible light excitation, the BeBeCO complex rearranges to a BeCOBe isomer, which further isomerizes to a low‐energy BeOBeC species under UV‐visible light excitation. These species are identified on the basis of infrared absorption spectroscopy with isotopic substitutions and quantum chemical studies. The BeOBeC molecule is characterized to be a multiple radical species having an electronic quintet ground state featuring an unusual quartet carbyne unit with three unpaired electrons on the carbon center. Bonding analysis indicates that the strong Pauli repulsion between carbon 2s lone pair electrons and the σ electrons of the BeOBe fragment significantly weakens the Be−C bonding and destabilizes the triplet state of the BeOBeC radical with a doublet carbyne unit. The three‐center π‐bonding of BeOBe is also found to play a role in stabilizing the quartet carbyne. Abstract : Für das multiple Radikal BeOBeC wird die Existenz einer Quartett‐Carbingruppe identifiziert. Es stellt das erste Carbin‐Radikal dar, das einen Quartett‐Grundzustand mit drei ungepaarten Elektronen am Kohlenstoffzentrum aufweist.